Trade Finance in Crisis : Should Developing Countries Establish Export Credit Agencies? - Chauffour, Jean-Pierre; Saborowski, Christian; Soylemezoglu, Ahmet I. (World Bank, Washington, DC, 2014)
New data on export insurance and guarantees suggest that publicly backed export credit agencies have played a role to prevent a complete drying up of trade finance markets during the current financial crisis. Given that export credit agencies are mainly located in advanced and emerging economies, the question arises whether developing countries that are not equipped with these agencies should establish their own agencies to support exporting firms and avoid trade finance shortages in times of crisis. This paper highlights a number of issues requiring attention in the decision whether to establish such specialized financial institutions. It concludes that developing countries should consider export credit agencies only when certain pre-requirements in terms of financial capacity, institutional capability, and governance are met.